The first-time trainer : a step-by-step quick guide for managers, supervisors, and new training professionals - Goad, Tom W. (AMACOM/American Management Association, 2010)
Successful organizations depend on training to keep them viablebut in today's belt-tightening economy, managers are often asked to become expert training facilitators overnight. Faced with the challenges of diversity, a multi-generational workforce, and the many options made possible by technology and e-learning, even first-time trainers must be ready with the most up-to-the-minute techniques. Thoroughly revised, The First-Time Trainer is a concise, information-packed guide that will quickly transform readers into confident, effective trainers. Filled with real-world examples and dozens of fi.